Competition in an Audit Segmented Market: Evidence from the Nigerian Listed Non-Financial Firms - INNEH, Eghosa Godwin; AYOOLA, Tajudeen John; OBOKOH, Lawrence Ogechukwu (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025, 2025)
The study examines the effect of competition on audit price and quality. We measure competition using initial audit price, static, and dynamic competition indicators. Static competition is measured using audit concentration, while the dynamic competition is measured using client mobility. The study fills in the gap in the literature by examining audit competition in a segmented audit market, considering audit complexity, and separating the Nigerian non-financial institution audit market into oligopolistic and atomistic segments. Our study employs ordinary least squares to analyse the data collected. The results show that audit concentration positively affects audit fees and improves quality in both segments. The study indicates that client mobility positively affects audit fees in both fragmented markets and provides evidence that audit clients react to low quality competitively by switching auditors within the segments. Finally, our results show that audit firms engage in lowball practices in the initial audit year as a marketing strategy, and initial year audit fee discounting improves audit quality. Our study provides evidence of competition within an audit-segmented market when the basis of delineation is audit complexity. Our results provide empirical evidence of audit competition in the oligopolistic segment, contrary to the traditional view of Structure Conduct Performance (SCP).